Predictors of tobacco abstinence in outpatient smokers with schizophrenia or bipolar disorder treated with varenicline and cognitive behavioral smoking cessation therapy. (August 2017) - Schuster, Randi M.; Cather, Corinne; Pachas, Gladys N.; Zhang, Haiyue; Cieslak, Kristina M.; Hoeppner, Susanne S.; Schoenfeld, David; Eden Evins, A.
Abstract: Background: The estimated mortality gap between those with and without serious mental illness (SMI) is increasing, now estimated at 28 years, which is largely due to smoking-related diseases. Aims: We sought to identify predictors of 14-day continuous abstinence in stable outpatient smokers with SMI. Method: Adult smokers with schizophrenia spectrum ( n = 130) or bipolar disorder ( n = 23) were enrolled in a 12-week course of varenicline and cognitive-behavioral therapy for smoking cessation. Results: Independent predictors of abstinence included reduction in withdrawal symptoms prior to the quit day, fewer cigarettes smoked per day at baseline, better baseline attention, remitted alcohol dependence, and lower expectation of peer support to aid quitting. Conclusions: Interventions that consider these targets may improve smoking cessation outcomes in those with SMI. Highlights: Smoking remains an epidemic among those with SMI, responsible for large disparities in mortality. Less withdrawal, smoking less, and attentional performance were associated with abstinence. Past alcohol dependence and anticipating less support were associated with abstinence.